Society, Community and Power in Northern Spain: 700-1000 - Portass, R (2011)
The period from c.718 to c.1000 oversaw the reconquest of a significant part of the Iberian Peninsula by the Kingdom of Asturias (718–910) and its successor in León (910–1037); the study of this process of Reconquista has in recent years focused on two broader social changes: the increasing exploitation of the peasantry, and the eclipse of public power. In the Introduction, I argue that it is necessary to integrate the study of peasant societies with analyses of royal and aristocratic power; reframing the subject in this way, we are able to appreciate the diversity of social experience which characterized both peasant and aristocratic life across the two case studies here examined, Southern Galicia, and the Liébana. I argue that the tenth century must be seen on its own terms, and without the benefit of hindsight, if we are to characterize it fairly. Chapter Two discusses the source material I have used in the elaboration of this thesis, highlighting its uses and problems from a critical perspective. In Chapter Three I show that fluid social structures allowed a family to rise to power from amongst the village inhabitants of the Liébana. Public officials such as counts were not able to impose themselves frequently upon this society. In Chapter Four, I show how a rich and aristocratic family of lay magnates, based in southern Galicia, were major political operators from the ninth century, but only came to exercise significant social influence amongst local society after the construction of the monastery of Celanova in 936. My Conclusion contextualizes these changes; it also argues that more nuanced and less schematic approaches to social relations demonstrate that peasants retained considerable autonomy in this period, and that factional politics influenced the stability of kingship far more than the supposed eclipse of public power.